On Asymptotically ?-Statistical Equivalent Sequences of Order ? in Probability - Akbas, Kubra Elif; Isik, Mahmut (Univ Nis, Fac Sci Math, 2020)
In this study, we introduce and examine the concepts of asymptotically lambda-statistical equivalent sequences of order alpha in probability and strong asymptotically lambda-equivalent sequences of order alpha in probability. We give some relations connected to these concepts.
Keywords: Statistical convergence of order alpha in probability; Cesaro summability of order ff in probability; asymptotic statistical equivalence